Corporate social responsibility practices of pharmaceutical companies in China: scale validity and reliability - Qian, Y.; Reis, E.; Chen, C. (XXIII Congresso da SPE, 2017)
In order to assess the Corporate Social Responsibility (CSR) practices of pharmaceutical companies in China, a reliable and credible measurement instrument has to be available. Currently there is no universally accepted definition of CSR, and existing theoretical models fail to fit either characteristics of the pharmaceutical industry or China’s cultural context. As a result, a new model has to be built that take both factors into account. This paper has the main purpose of designing an original and valid scale for measuring the CSR practices of pharmaceutical companies in China. Various researchers have proposed different definitions of CSR, but a universally accepted description is still absent [4]. Amongst theories concerning CSR, the stakeholder theory [3] and Carroll’s four-dimensional model are frequently adopted. ‘CSR serves as an internal, self-regulating mechanism by which the enterprise examines and practices full compliance with law, ethical requirements, and international standards. It is a process to implement responsibility for its actions and ensures positive influence on its stakeholders’ [2]. Unlike the cases in many other industries, the products of pharmaceutical companies directly affect the health, well-being and even lives of people, involving subtle ethical issues. So, violations of CSR norms by pharmaceutical companies can be more costly and destructive. Before appropriate strategies can be devised, the following question must be unambiguously answered: Is a scale the most appropriate and viable method to assess the CSR practices? How should its reliability and validity be ensured? This research combines Carroll’s model with the stakeholder theory to answer the previous question. The standard procedure of the Grounded Theory [1] was used starting with 105 face-to-face in-depth interviews on both internal and external stakeholders: top and middle managers, employees from pharmaceutical companies in 5 Chinese provinces; patients with chronic diseases in three general hospitals in Hangzhou; doctors from two general hospitals and one community clinic in Hangzhou; officials at the Zhejiang Provincial Food & Drug Administration; and middle managers at two Active Pharmaceutical Ingredient (API) manufacturers. Simultaneously, open-ended questionnaires were sent to a sample of 100 respondents from the same previously described groups. The information collected was submitted to the usual content analysis procedure (open, axial and selective coding) and results were used to design the first draft of the scale. 12 experts were invited to discuss, filter and optimize the scale, which was then pre-tested on a sample of 101 of workers of pharmaceutical companies. The final version of the scale was distributed to 320 top and middle managers of about 180 Chinese pharmaceutical companies, and a total of 298 valid questionnaires was returned. Evaluation of reliability, content and construct validity of the CSR measurement model included the calculation of the Corrected Item-Total Correlation, Cronbach Alpha Coefficient, Exploratory and Confirmatory Factor Analyses. Convergent validity was determined by examining the Standardized Factor Loadings, the Average Variance Extracted (AVE) and the Composite Reliability. Discriminant Validity was evaluated by comparing the square roots of the AVE for every dimension and the absolute values of their correlation coefficients with other dimensions. An eight-dimensional and 36-item measurement tool was validated. The eight initial dimensions (Shareholders, Managers and Employees; Creditors & Suppliers, Patients & Doctors; Government, Environment and Local Community) allowed the identification of 3 higher-order dimensions: CSR for internal parties, CSR for external partners and CSR for public entities. Finally, a definition of CSR of pharmaceutical companies in China is proposed.